Angelman Syndrome and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Characteristic epileptic seizures and EEG abnormalities are reported in three siblings with Angelman syndrome from the Kansai University Otokoyoma Hospital, Kyoto; and the Nagasaki University School of Medicine, Japan.